Combating Corruption Based on Community Participation in Urban PNPM Mandiri in Sidoarjo Regency - Hazim Hazim (Universitas Muhammadiyah Sidoarjo, 2013)
A prevention of corruption in Indonesia through structural approach has been examined by many scholars. The gap is, there is not found a study related to this issue focusing on cultural approach. For this reason, this study is concentrated on the public participation in order to prevent the corruption which focuses on the Urban Poverty Projects (PNPM Mandiri Perkotaan) in Sidoarjo, East Java, as a case study. The research questions are: a) to what extend the community base participant impacts the reduce corruptions?; b) what are the modes of public participation in order to prevent the corruptions?. The aim of this study investigates the mode of community participations in order to minimize the corruption. A descriptive qualitative approach was used to collect the data which used three main methods: a) observation concentrated at two sub-districts, Taman and Sidoarjo; b) interview conducted for getting valuable information from the program executors and beneficiaries of “PNPM Mandiri Perkotaan” as well; c) a study of documents related to the program such as the standart operational procedures (SOPs) as well as proposal and report documents. Some theoretical framewoks of participations have been used to analyse the data. The results of this study can be seen that there are three stages of public participation in order to prevent the corruption: the first is the plan stage. Generally, public still need to be forced to participate at this step. However public have showed significant participations through thought and physical participation with skills. The second is the implementation stage. Public have been able to do self-mobilization participation including physical, psychological participation and participation with skills at this step. Moreover, they also have contributed significantly through financial participation instead of getting income from their involments. However, in the last step called monitoring and evaluation, they generally need to be encouraged by external factors to participate in this stage. Regularly meeting is a part of their participation in order to evaluate their projects.